Exergo-ecological analysis and life cycle assessment of agro-wastes using a combined simulation approach based on Cape-Open to Cape-Open (COCO) and SimaPro free-software. (December 2022) - Zalazar-Garcia, Daniela; Fernandez, Anabel; Rodriguez-Ortiz, Leandro; Torres, Erick; Reyes-Urrutia, Andrés; Echegaray, Marcelo; Rodriguez, Rosa; Mazza, Germán
Abstract: Thermochemical processes to convert bio-wastes into valuable products and bioenergy have been extensively studied in the literature. Experimental and, to a lesser extent, rigorous simulation papers concerning these processes have been widely considered and discussed in the literature. Nonetheless, there is still a gap to fill in providing a fast and reliable simulation scheme. In this paper, an efficient simulation strategy, combining the free-software COCO simulator for the bio-waste slow pyrolysis coupled with commercial SimaPro code to carry out the Life Cycle Assessment (LCA), was applied. The pyrolysis product yields at 673, 773, and 873 K were well predicted using mass and energy balances and a proposed reaction scheme from the literature. Simulations were validated using experimental data previously reported. The highest yield was 53.7% for biochar (673 K – stalk of white grape), 32% for bio-oil (773 K - marc of red grape), and 56.3% for gas (873 K - marc of white grape). The results from LCA and cumulative exergy demand (CExD) were useful to detect and reduce environmental impacts in previous stages of the process. Graphical abstract: Image 1